ELECTRO-GEODYNAMICAL PHENOMENA IN ATMOSPHERE AND THEIR INFLUENCE ON THE MASS EXCHANGE - BUBLIAS, V.; SHESTOPALOV, V.; BUBLIAS, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The problem questions of the principle formation of electric phenomena (electromagnetic force, strain and strength of electric current), their variation in space and time, and influence on the mass exchange between the atmosphere and lithosphere are considered. The experimental data obtained in laboratory and field conditions are represented. The results of works show the dependence of the liquid phase movement in the covering deposits (in samples of undisturbed structure) on variations of definite electric potentials formed in the atmosphere and lithosphere.